2002
DOI: 10.1006/mthe.2002.0541
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Transduction of Human Dendritic Cells with Optimized SIV Vectors

Abstract: As major antigen-presenting cells and effectors in the maintenance of tolerance, dendritic cells (DCs) are key cells of the immune system and can thus be envisioned to have roles in immunotherapy strategies. We, and others, previously showed that simian immunodeficiency virus (SIV)-derived lentiviral vectors were able to deliver a gene into human differentiated DCs. We describe here the upgrading of the SIV vector system and the improvements of the transduction protocol, which allowed us to transduce more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(113 citation statements)
references
References 38 publications
2
110
1
Order By: Relevance
“…Additionally, the incorporation of the WPRE element in EIAV vectors had no effect in primary human hematopoietic cells and was slightly inhibitory in mouse muscle in vivo (data not shown). 16 Mangeot et al 21 reported that WPRE significantly reduced gene transfer to primary human dendritic cells in the context of SIV vectors. These data suggest the use of the WPRE elements should be investigated in a cell type and vector specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the incorporation of the WPRE element in EIAV vectors had no effect in primary human hematopoietic cells and was slightly inhibitory in mouse muscle in vivo (data not shown). 16 Mangeot et al 21 reported that WPRE significantly reduced gene transfer to primary human dendritic cells in the context of SIV vectors. These data suggest the use of the WPRE elements should be investigated in a cell type and vector specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…21 Therefore, we investigated the viral constitutive transport elements (CTE) from the Mason-Pfizer monkey virus; the direct repeat 1 element (DR1) from the Rous sarcoma virus and the woodchuck hepatitis virus post-transcriptional regulatory element (WPRE) in the context of EIAV vectors. Transduction of the T-cell lines with either the CTE or DR1 containing vectors increased the number of EGFP positive cells between three-and approximately five-fold (Table 1).…”
Section: Addition Of Post-transcriptional Elements Into Eiav Vectors mentioning
confidence: 99%
“…Nevertheless, the transduction of human dendritic cells (DCs) may require the presence of vpx [25]. In the context of FIV-derived LV vectors, Johnston et al [26] have removed the accessory genes encoding vif and orf2 from the packaging construct without observing any decrease in the particle production.…”
Section: Removal Of Accessory Genesmentioning
confidence: 99%
“…Interestingly, they have shown that the WPRE was significantly more active than its HBV counterpart; this increased activity may correlate with the presence of an additional cis-acting sequence in the WPRE which is not found in the HPRE. Surprisingly, while the insertion of the WPRE in SIV-derived vectors has also been shown to increase transgene expression in 293T cells, its presence seemed to be detrimental to gene transfer in human DCs [25]. Relative to the EIAV-based system, the addition of the WPRE cis-acting sequence to vectors markedly increased gene expression in mouse skeletal muscle cells [57].…”
Section: Incorporation Of Additional Cis-acting Regulatory Sequencesmentioning
confidence: 99%
See 1 more Smart Citation